Korean Division Films - Eunjin Choi (Encyclopedia, 2022)
As one half of what is currently the only divided country in the world, the phenomenon of the so-called “division film” in South Korea has developed as a reflection of the social changes associated with its divided national background. The divided Korean Peninsula, the cause of military confrontation between the two Koreas, the Korean War, and espionage activities, is the background for Korean division films. As a result, the divided state serves as a narrative element and can be explored as a theme. Since the release of the first division films in 1949, a year after the Korean Peninsula was split into two countries, division films have been produced constantly. This entry analyzes major political changes, focusing on the regime changes represented in division films and, based on this approach, explores the cinematic illustrations of modern Korean history in three distinct periods. In a bid to reflect the characteristics of the times, division films portray historical elements while acting successfully as an advanced form of art. Herein, I will examine the definition and the range of these division films. This entry thus aims to discuss, in depth, the origin and history of Korea’s division films.